A Review of the Popular and Scholarly Accounts of Donald Trump’s White Working-Class Support in the 2016 US Presidential Election - Jack Thompson (Societies, 2019)
Popular and scholarly accounts of Trump’s ascendency to the presidency of the United States on the part of the American white working-class use different variables to define the sociodemographic group because there is no “working-class White„ variable available in benchmark datasets for researchers to code. To address this need, the Author ran a multinomial regression to assess whether income, education and racial identity predict working-class membership among white Americans, finding that income and education are statistically significant predictors of working-class whiteness, while racial identity is not. Arriving at a robust definition of “white working-class„ in light of these findings, the paper next turns to a review of the extant literature. By retrieving studies from searches of computerised databases, hand searches and authoritative texts, the review critically surmises the explanatory accounts of Trump’s victory. Discussion of the findings from the review is presented in three principal sections. The first section explains how working-class White communities, crippled by a dearth of social and geographic mobility, have been “left behind„ by the political elites. The second section examines how white Americans, whose dominant group position is threatened by demographic change, voted for Trump because of resonance between his populist rhetoric and their latent “racist„ attitudes. The third and final section explores the implications of a changing America for native-born whites, and how America’s increasing ethnoracial diversity is eroding relations between its dominant and nondominant groups. The Author surmises by arguing that these explanatory accounts must be understood in the context of this new empirical approximation of “working-class White„.